The effect of work-life balance on work engagement mediated by job satisfaction and life satisfaction: Study on Balai Pemasyarakatan kelas I Denpasar’s employee - Pramana, I Gusti Ngurah Agung Aditya; Putra, Made Surya (International research journal of management, IT and social sciences, 2022)
This study aims to examine the effect of work-life balance on Work engagement mediated by job satisfaction and life satisfaction in BAPAS Class I Denpasar employees. The sample size used in this study was 50 people with the method of determining the sample, namely saturated sampling. The data were analyzed by using the PLS-based SEM analysis technique. The results showed that work-life balance had an insignificant negative effect on work engagement, job satisfaction had a significant positive effect on work engagement, life satisfaction had a positive and insignificant effect on work engagement, the work-life balance had a significant positive effect on job satisfaction, and work-life balance had a significant positive effect on work engagement. significantly positive on life satisfaction, job satisfaction mediates the effect of work-life balance on work engagement, and life satisfaction does not mediate the effect of work-life balance on work engagement. It is recommended that companies understand the needs of work-life balance, job satisfaction and employee life satisfaction so as to increase Work engagement.